Shariah Compliance Screening Moderating Effect on Risk and Return: The Malaysian Case of Capital Market - Bakri, Mohd Ashari (Journal of King Abdulaziz University: Islamic Economics, 2023)
The objective of this paper is to determine the moderating effect of Sharīʿah-compliant securities on the relationship between risk and return. The study uses panel regression, pooled ordinary least squares (OLS), random and fixed effects analysis. The sample size of the study consists of the 200 largest companies based on the list of market capitalization in 2019. In addition, the study uses a firm fixed effect and a two-stage generalized moments method (GMM) to test the robustness of the results for the years between 2010 and 2019 in Malaysian companies. The results show that Sharīʿah-compliant securities negatively affect the relationship between risk and stock returns. The results are robust, even after mitigating endogeneity issues regarding omitted variable bias and reverse causality. The author argues that Sharīʿah compliance acts as a mechanism to mitigate the relationship between risk and return. Policy makers such as the government could promote the benefits of Sharīʿah-compliant securities in the Islamic capital market (ICM) to mitigate the risk-return relationship. The government should promote ICM as a hub for Sharīʿah-compliant investment portfolios with this advantage to encourage more investors to choose ICM as their main preference for an internationally diversified portfolio. It is believed that previous research has not considered Sharīʿah compliance as a moderating factor in the relationship between risk and equity returns. This gap has been addressed in this study.